ANALYSIS OF HYPERBOLE MAJAS IN THE LYRICS OF THE SONG LEMON BY KENSHI YONEZU AND NEKO BY TAKUMI KITAMURA - Fitrah Magfirah Marwah Zainal (Universitas WIdyatama, 2022)
Music is a beautiful tone and voice that contains rhythm, song, and the harmony of sound. In every song, there must be a figurative language. Majas (figurative language) is a medium in language that is useful in the process of delivering messages or presenting a certain idea. One of the figurative language types is hyperbole. Hyperbole is a figurative language which is an exaggerated expression. After being researched, the author found many hyperbole in various forms. This study used the theory by Sato to analyze hyperbole figurative language. The source of the data in this study is a Japanese song, namely Lemon by Kenzi Yonezu and Neko by Takumi Kitamura. The method of data collection used in this study is the observational method using a note-taking technique. Whereas the analysis used the referential method with the PUP technique (Teknik Pilah Unsur Penentu). Based on the results of the analysis of the hyperbole found in the song Lemon by Kenzi Yonezu and Neko by Takumi Kitamura, it can be concluded that there are 57 data of hyperbole, including in Lemon by Kenzi Yonezu with 27 data of hyperbole figurative language were found, and in Neko by Takumi Kitamura with 30 data of hyperbole figurative language were found. In this study, the hyperbole which is widely used in songs Lemon and Neko is the hyperbole that is related to feelings with 21 data found.